Consumption Inequality and Family Labor Supply - Blundell, Richard; Pistaferri, Luigi; Saporta-Eksten, Itay (American Economic Review, 2016)
We examine the link between wage and consumption inequality using a life-cycle model incorporating consumption and family labor supply decisions. We derive analytical expressions for the dynamics of consumption, hours, and earnings of two earners in the presence of correlated wage shocks, nonseparability, progressive taxation, and asset accumulation. The model is estimated using panel data for hours, earnings, assets, and consumption. We focus on family labor supply as an insurance mechanism and find strong evidence of smoothing of permanent wage shocks. Once family labor supply, assets, and taxes are properly accounted for there is little evidence of additional insurance. (JEL D12, D14, D91, J22, J31)